Manajemen Kegiatan Keagamaan di MTs Terpadu Berkah - Sahrul Iman Bhato; Abdul Norafnan (PT. PENERBIT TIGA MUTIARA, 2024)
Religious activity management at MTs Terpadu Berkah Palangka Raya is an integral part of education aimed at developing students holistically, including spiritual and moral aspects. Through a planned and structured management approach, this school has effectively implemented religious activities, covering planning, implementation, and supervision aspects. The religious management at MTs Terpadu Berkah is based on Islamic principles and implemented through harmonious coordination among the implementers. Careful supervision is conducted by the headmaster and educators to ensure the smoothness and compliance with the work plans and the school's vision and mission. Thus, religious activities at MTs Terpadu Berkah are not only school routines but also crucial means in shaping the character and morals of students, as well as strengthening their bonds with religious values. The implementation of religious activities at MTs Terpadu Berkah is supported by effective coordination among all team members, guided by the headmaster and educators. Through meticulous supervision, every step in the implementation of activities is evaluated and improved to ensure compliance with the established plans. Supervision not only focuses on material aspects but also considers the spiritual dimension to maintain consistency with religious values. With strict supervision, every team member is motivated to achieve the established goals, so that religious activities can proceed as expected and have a positive impact on students and the school environment as a whole. Therefore, good religious management at MTs Terpadu Berkah not only creates a conducive learning atmosphere but also shapes students into morally upright and spiritually aware individuals.